Decolonising the Nigerian Curriculum: a Path to Self-Reliant Education (2023)
The process of education is pivotal to the development of any society as no nation can rise beyond the level of her educational development. Curriculum is an important aspect of education; it determines the quality of educational System of any society. The Nigerian education System has suffered great setbacks due to the dysfunctional curriculum which it operates over the years. It has been established that effects of colonisation can still be felt in the Nigerian education sector which had continued to depend on the curriculum handed over from the colonial masters, which had rendered graduates of various institutions unqualified or 'half-baked' and unfit to meet the demands of their society. There has been economies underdevelopment as well as increased dependence on foreign technology. Previous researches have suggested modification of the curriculum as an antidote; however, this has not really yielded expected results due to poor commitment, perpetual change in policies and politicisation of educational decisions. This study adopted the method of philosophical discourse to examine the need to embark on decolonisation of the curriculum as a necessary means to resolve the situation and promote educational sustainability. The paper recommended that learning contents should be made to fit into the practical experiences of the Nigerian society; vocational skills should be inculcated into school activities/learning experiences, traditional values need to be promoted, while indigenous language should be employed alongside English language as modes of communication in schools to promote better understanding among learners.